2021
DOI: 10.3390/a14030077
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Task Scheduling Optimization in Spatial Crowdsourcing

Abstract: Recently, with the development of mobile devices and the crowdsourcing platform, spatial crowdsourcing (SC) has become more widespread. In SC, workers need to physically travel to complete spatial–temporal tasks during a certain period of time. The main problem in SC platforms is scheduling a set of proper workers to achieve a set of spatial tasks based on different objectives. In actuality, real-world applications of SC need to optimize multiple objectives together, and these objectives may sometimes conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The contribution of the study shows that the proposed scheduling approach makes the task mapping perform in a better manner. Alabbadi and Abulkhair [34] proposed a novel Multi‐Objective Particle Swarm Optimisation (MOPSO) algorithm for multi‐objective task scheduling on cloud data centres, and the results showed that MOPSO can find the optimal solution and outperform other existing single and multi‐objective scheduling algorithms. Generally, previous studies only focussed on makespan [35, 36] and power usage [37, 38] in the scheduling process, or only considered the load balancing [39, 40], and employed certain algorithms to achieve multi‐objective [41, 42] or single‐objective optimisation.…”
Section: Related Workmentioning
confidence: 99%
“…The contribution of the study shows that the proposed scheduling approach makes the task mapping perform in a better manner. Alabbadi and Abulkhair [34] proposed a novel Multi‐Objective Particle Swarm Optimisation (MOPSO) algorithm for multi‐objective task scheduling on cloud data centres, and the results showed that MOPSO can find the optimal solution and outperform other existing single and multi‐objective scheduling algorithms. Generally, previous studies only focussed on makespan [35, 36] and power usage [37, 38] in the scheduling process, or only considered the load balancing [39, 40], and employed certain algorithms to achieve multi‐objective [41, 42] or single‐objective optimisation.…”
Section: Related Workmentioning
confidence: 99%
“…Kumar et al proposed a generalized ant colony optimizer algorithm (GACO) to solve the cloud resource allocation problem [14]. Alabbadi et al proposed multi-objective task scheduling optimization (MOTSO) to find the optimal solution [15], which solved the optimization problem well. Cao et al proposed a depth optimization analysis method based on the GA algorithm [16].…”
Section: Introductionmentioning
confidence: 99%